Effect of 5:2 intermittent fasting diet versus daily calorie restriction eating on metabolic-associated fatty liver disease—a randomized controlled trial - Wang, Yuan-yuan; Tian, Fang; Qian, Xiao-lu; Ying, Hui-min; Zhou, Zhen-feng (Frontiers in Nutrition, 2024)
Objective: Both 5:2 IF diet (intermittent fasting) and daily caloric restriction eating had been suggested for management of MAFLD (Metabolic-Associated Fatty Liver Disease), this study aimed to evaluate the effects of 5:2 IF diet on body weight and metabolic parameters in adults with MAFLD, in comparison to daily caloric restriction eating. Methods: This single-center, double-blind, prospective, randomized controlled trial included 60 patients with MAFLD, who were administered either a 5:2 IF diet limited calories consumed for 2 days each week with no restrictions on the remaining 5 (Group 5:2 IF diet) or a daily calorie restriction eating (Group daily calorie restriction). Fibrotouch-B instrument assessment, ultrasound assessment of hepatic steatosis, anthropometric indices and body composition analysis, blood sample measurements were conducted during two distinct visits: initially on the day of study commencement (T1), and subsequently at the conclusion of the 12-week intervention period (T2). Results: In comparison to daily calorie restriction eating, the 5:2 IF diet significantly decreased the proportion of hepatic steatosis ≥moderate (29.6% vs. 59.3%, p =0.028) and the degree of hepatic fibrosis F ≥ 2 (3.7% vs. 25.9%, p =0.05), and fewer percentage of patients were diagnosed with fatty liver via upper abdominal ultrasound in the 5:2 intermittent fasting diet group (33.3% vs. 63.0%, p =0.029). Additionally, the CAP (controlled attenuation parameter) and LSM (liver stiffness measurernents) value were significantly lower in the 5:2 IF diet group (p <0.05). No statistically significant differences were observed between the two groups in terms of weight, BMI (body mass index), WC (waist circumference), HC (hip circumference), and WHR (waist to hip ratio). Similarly, there were no significant differences in lipid profile, glycemic indices and adverse events (p>0.05). Conclusions: In summary, although both 5:2 IF diet and daily caloric restriction eating achieved similar effect on body weight, liver enzymes, lipid profile and glycemic indices after 12 weeks treatment, 5:2 IF diet demonstrates better improvement in fibrosis and steatosis scores independently from weight regulation. Consequently, it is anticipated to emerge as a viable dietary modality for lifestyle intervention among patients diagnosed with MAFLD.